Conflict and consensus a general theory of collective decisions - Moscovici, Serge (Sage Publications, 1994)
Presents a theory of the processes of collective decision-making that draws on theoretical influences, ranging from group decision theory to the authors' social representations theory. The text offers an analysis of group conflict and consensus to produce a general theory of collective decisions.